(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to define the concept of accounting measurement for sustainable development and highlight its various methods, as well as to analyze the relationship between accounting measurement for sustainable development and financial reporting. Furthermore, the study examines the impact of this relationship on the quality of accounting information. The research adopts a descriptive-analytical approach and includes an applied study on the Iraqi Cement State Company as a case study. Data were collected from the company’s annual reports and interviews with officials to analyze its environmental and social performance. The study concluded that the company places significant emphasis on healthcare, occupational safety, and civil defense services. However, it neglects critical environmental aspects, such as noise control, ventilation quality, temperature management, and airborne dust. Additionally, the company lacks a comprehensive plan or a clear vision to ensure long-term environmental integration. The research also revealed that the production process, particularly the burning phase, emits harmful gases that adversely affect the health of employees and the surrounding community, highlighting the need for advanced systems to monitor and manage environmental impacts. The research recommends integrating environmental and social performance indicators, such as waste management costs, gas emissions, and preventive measures, into financial statements and annual reports. This integration would enhance the transparency and credibility of accounting information for investors and stakeholders. Moreover, the study emphasizes the importance of developing a comprehensive environmental strategy to address various environmental issues and align them with the company’s long-term financial plans, thereby improving environmental performance and fostering sustainability